A longitudinal investigation of performance and injury outcomes associated with disordered eating in elite athletes - Fatt, S. J.; Hay, P.; George, E.; Jeacocke, N.; Rogers, K.; Mitchison, D. (Sports Medicine - Open, 2025)
Background Disordered eating is common in elite athletes and may be motivated by perceived performance advantages associated with becoming leaner. However, few studies have examined the performance outcomes associated with disordered eating over time in this population. This study investigated self-reported performance and days missed from training/competition due to injury as longitudinal outcomes of disordered eating.